Evaluating the Risk of Breast Cancer Recurrence and Metastasis After Adjuvant Tamoxifen Therapy by Integrating Polymorphisms in Cytochrome P450 Genes and Clinicopathological Characteristics - Pang, Hui; Zhang, Guoqiang; Yan, Na; Lang, Jidong; Liang, Yuebin; Xu, Xinyuan; Cui, Yaowen; Wu, Xueya; Li, Xianjun; Shan, Ming; Wang, Xiaoqin; Meng, Xiangzhi; et al. (Frontiers in Oncology, 2021)
Tamoxifen (TAM) is the most commonly used adjuvant endocrine drug for hormone receptor-positive (HR+) breast cancer patients. However, how to accurately evaluate the risk of breast cancer recurrence and metastasis after adjuvant tamoxifen therapy is still a major concern.In this study, we aimed to first develop and validate an algorithm combining polymorphisms in CYP genes and clinicopathological signatures to identify a subpopulation of breast cancer patients who might benefit most from TAM adjuvant therapy, and meanwhile evaluate major risk factors related to TAM-resistance. Specifically, a total of 256 patients with invasive breast cancer who received adjuvant endocrine therapy were selected. The genotypes at ten loci from three tamoxifen metabolism-related CYP genes were detected by time-of-flight mass spectrometry and multiplex long polymerase-chain-reaction. Combining the 10 loci with 9 clinicopathological characteristics, we obtained 19 important features, whose association with cancer recurrence was assessed by importance score via random forests. After that, a logistic regression model was trained to calculate TAM Risk-of-recurrence score (TAM RORs), which is adopted to assess a patient’s risk of recurrence after TAM treatment. The sensitivity and specificity of the model in an independent test cohort were 86.67% and 64.56%, respectively. This study showed that breast cancer patients with high TAM RORs were less sensitive to TAM treatment and manifested more invasive characteristics, whereas those with low TAM RORs were highly sensitive to TAM treatment and their conditions were stable during the follow-up period. There were some risk factors which had significant effect on the efficacy of TAM. They were tissue classification (tumor Grade<2 vs Grade≥2, P=2.2e-16.), the number of lymph node metastases (Node-Negative vs Node<4, P=5.3e-07; Node<4 vs Node ≥ 4, P=0.003; Node-Negative vs Node ≥ 4, P=7.2e-15), the expression levels of ER and PR (ER<50% vs ER≥50%, P=1.3e-12; PR<50% vs PR≥50%, P=2.6e-08). The really remarkable thing is that different genotypes of CYP2D6*10 (C188T) show significant differences in prediction function (CYP2D6*10 CC vs TT, P<0.019; CYP2D6*10 CT vs TT, P<0.037). There are more than 50% Chinese whose have CYP2D6 * 10 mutation. So, the genotype of CYP2D6*10 (C188T) should be tested before TAM therapy.